Naïve or Engineered Extracellular Vesicles from Different Cell Sources: Therapeutic Tools for Kidney Diseases - Elena Ceccotti; Gabriele Saccu; Maria Beatriz Herrera Sanchez; Stefania Bruno (MDPI AG, 2023)
Renal pathophysiology is a multifactorial process involving different kidney structures. Acute kidney injury (AKI) is a clinical condition characterized by tubular necrosis and glomerular hyperfiltration. The maladaptive repair after AKI predisposes to the onset of chronic kidney diseases (CKD). CKD is a progressive and irreversible loss of kidney function, characterized by fibrosis that could lead to end stage renal disease. In this review we provide a comprehensive overview of the most recent scientific publications analyzing the therapeutic potential of Extracellular Vesicles (EV)-based treatments in different animal models of AKI and CKD. EVs from multiple sources act as paracrine effectors involved in cell-cell communication with pro-generative and low immunogenic properties. They represent innovative and promising natural drug delivery vehicles used to treat experimental acute and chronic kidney diseases. Differently from synthetic systems, EVs can cross biological barriers and deliver biomolecules to the recipient cells inducing a physiological response. Moreover, new methods for improving the EVs as carriers have been introduced, such as the engineering of the cargo, the modification of the proteins on the external membrane, or the pre-conditioning of the cell of origin. The new nano-medicine approaches based on bioengineered EVs are an attempt to enhance their drug delivery capacity for potential clinical applications.